Mobilities, individuation, and agencies: An analysis based on young migrants’ biographical narratives in Buenos Aires, Argentina - Tapia, Silvia Alejandra (2021)
Social studies point out the unequal conditions for moving or staying, internally or internationally, that young people from different social sectors face in their biographies. In this article, we analyze the migratory experiences of young people from popular sectors of the Metropolitan Area of Buenos Aires, Argentina. To do that, we put into dialogue recent studies on migration and proposals of the sociology of individuation and the new mobility paradigm. We approach the individuation processes of these young people through the qualitative analysis of their biographical narratives in which their migration experiences emerged as turning points in their lives. The article argues that young migrants from popular sectors draft their agencies and shape themselves as individuals by mobilizing material and symbolic supports and accessing different social shock-absorbers that allow them to cope with three major social challenges in their migratory processes: the socio-labor trial; the family trial, and the identity trial. By identifying the discontinuities and the common evidence present in the migratory experiences of these young people and their families, the paper ends highlighting the articulations among coercions, elasticities, and strategies that these youth migrant mobilize, individually and collectively, around themselves and others, through border-links to create shelters and deal with such challenges.